Integrative Studies of Human Cord Blood Derived Mononuclear Cells and Umbilical Cord Derived Mesenchyme Stem Cells in Ameliorating Bronchopulmonary Dysplasia - Chen, Jia; Chen, Yuhan; Du, Xue; Liu, Guojun; Fei, Xiaowei; Peng, Jian Ru; Zhang, Xing; Xiao, Fengjun; Wang, Xue; Yang, Xiao; Feng, Zhichun (Frontiers in Cell and Developmental Biology, 2021)
Bronchopulmonary dysplasia (BPD) is a common pulmonary complication observed in preterm infants that is composed of multifactorial pathogenesis. Current strategies, albeit successful in moderately reducing morbidity and mortality of BPD, failed to draw overall satisfactory conclusion. Here, using a typical mouse model mimicking hallmarks of BPD, we revealed that both cord blood-derived mononuclear cells (CB-MNCs) and umbilical cord-derived mesenchymal stem cells (UC-MSCs) are efficient in alleviating BPD. Notably, infusion of CB-MNCs has more prominent effects in preventing alveolar simplification and pulmonary vessel loss, restoring pulmonary respiratory functions and balancing inflammatory responses. To further elucidate the underlying mechanisms within the divergent therapeutic effects of UC-MSC and CB-MNC, we systematically investigated the long noncoding RNA (lncRNA)–microRNA (miRNA)–messenger RNA (mRNA) and circular RNA (circRNA)–miRNA–mRNA networks by whole-transcriptome sequencing. Importantly, pathway analysis integrating Gene Ontology (GO)/Kyoto Encyclopedia of Genes and Genomes (KEGG)/gene set enrichment analysis (GSEA) method indicates that the competing endogenous RNA (ceRNA) network is mainly related to the regulation of GTPase activity (GO: 0043087), extracellular signal-regulated kinase 1 (ERK1) and ERK2 signal cascade (GO: 0070371), chromosome regulation (GO: 0007059), and cell cycle control (GO: 0044770). Through rigorous selection of the lncRNA/circRNA-based ceRNA network, we demonstrated that the hub genes reside in UC-MSC- and CB-MNC-infused networks directed to the function of cell adhesion, motor transportation (Cdk13, Lrrn2), immune homeostasis balance, and autophagy (Homer3, Prkcd) relatively. Our studies illustrate the first comprehensive mRNA–miRNA–lncRNA and mRNA–miRNA–circRNA networks in stem cell-infused BPD model, which will be valuable in identifying reliable biomarkers or therapeutic targets for BPD pathogenesis and shed new light in the priming and conditioning of UC-MSCs or CB-MNCs in the treatment of neonatal lung injury.